Discernment: the message of the Bhagvad-Gita - K. Perumpallikunnel (Acta Theologica)
The Bhagavad-Gita is an intelligent response to a perennial human predicament which other religions and philosophies also tried to resolve in their own way. Human beings often stood perplexed and mystified as they confronted paradoxical situations in life that demanded action. Discerning right from wrong often became an existential predicament. The Pandava prince Arjuna found himself standing on the shaky ground of Kurukshetra not knowing the way forward. Lord Krishna outlines for him the path towards gaining flawless self-knowledge and self-mastery from his sorrowful state of confusion and opened his eyes to perceive the truths beyond appearances. Krishna instructs him that, when a person is capable of watching everything that happens within and around him dispassionately and acting with an attitude of detachment, he attains sthithaprajna (equanimity) and samadhai (liberation).